Regional integration and the euro crisis: problems and solutions - Argentino Pessoa (European Regional Science Association (ERSA), 2013)
Along time the European Union (EU) has been pointed as the most succeeded example of regional integration. Now, this example has been cruelly shaken by the EZ (Euro Zone) crisis, originating increasing doubts about the integration process. It is evident that the proposed solutions for attacking the crisis have hurt the European cohesion making more and more clear the separation of two big regions: one composed by North and Central European countries and the other constituted by the Southern and South-western countries. Why regardless of the uncountable meetings announced as decisive for its solution, and the recurrent EU proclamations of ?policies to restore European growth?, the crisis in the EZ looks more and more like an endless problem? Our paper deals with answers to this question emphasizing some problems affecting the solution to the EZ crisis. Some of them are political while others result from misconceptions about putting in place the correct economic policy. Given the enormous private and public debt accumulated in periphery after the single currency inception, and aggravated by the first attack to the international financial crisis, it is not questionable the need of fiscal consolidation in peripheral countries. Our paper shows why is erroneous to consider budgetary contraction as the only way of attaining fiscal consolidation and explains why austerity is so fiercely advocated by both core and periphery governments. The main reasons for the lack of competitiveness in periphery are explained and the possible options to minimize the structural imbalance inside EZ, between its core and periphery, are indicated. Our paper shows that the solutions to the EZ crisis applied by national governments, in cooperation with the European Commission, the ECB and the IMF, based on further austerity and wage cuts aggravate the crisis, instead of solve it. Such solutions are unlikely to reduce both sovereign and external debt ratios of periphery countries, but surely they will drive Euro Area as a whole to stagnation and lost decades of economic growth, if not to its disintegration. Considering the debt crisis as a problem of the PIIGS (Portugal, Ireland, Italy, Greece, Spain) that can be contained in the periphery is not the most adequate perspective either for solving the crisis or for the credibility of the EU integration process and will inevitably impact on the spreading of the integration model to other regions of the world.
Keywords: 330; Austerity; Euro crisis; Economic Growth; Euro Zone; EMU; Fiscal consolidation; Solvency